Prognostic value of disease distribution in secondary central nervous system diffuse large B cell lymphoma treated with radiation therapy. Issue 10 (24th August 2021) - Al Feghali, Karine A.; Fang, Penny; Gule-Monroe, Maria; Milgrom, Sarah; Khoury, Joseph D.; Gunther, Jillian R.; Sheu, Tommy; Nair, Ranjit; Ahmed, Sairah; Steiner, Raphael; Strati, Paolo; Shpall, Elizabeth J.; et al.
Abstract: This study aimed to assess the prognostic value of baseline disease distribution for patients with the secondary central nervous system (CNS) diffuse large B-cell lymphoma (DLBCL) treated with chemotherapy and radiation (RT). 44 patients with secondary CNS DLBCL were reviewed. Twenty patients had leptomeningeal disease (LMD), and 24 had localized/targetable disease (LTD). Of 8 patients who received stem cell transplantation (SCT) after RT, 6 had LTD with a complete or partial response after RT. Median time to CNS relapse after RT was 10.1 months; 3/24 patients with LTD and 5/15 with LMD had CNS relapse. The median overall survival (OS) was 8 and 20 months for patients with LMD and LTD, respectively ( p  = 0.20). On multivariable analysis, LTD, receipt of SCT, and response after RT were associated with better OS and CNS-disease-free survival. Patients with localized secondary CNS DLBCL may benefit from RT serving as a bridge to SCT.